Transformation of Islamic Boarding Schools as Islamic Education Institutions in Indonesia - Ahmad Musaddad (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2023)
Islamic boarding schools in Indonesia, known as